Penyusunan Instrumen Tes Prestasi Mata Pelajaran Matematika Pada Siswa Kelas 5 Sekolah Dasar - Wanesti, Nabilah Silvania; Setiawan, Roni; Sabaro, Rosyida Maya; Harsono, Yudi Tri (Flourishing Journal, 2024)
Academic achievement tests are important instruments to measure a person's academic success. The purpose of this study was to determine the development of mathematics achievement tests for grade V elementary school. The respondents of this study were fifth-grade students of public elementary schools in Malang City. The data analysis method was carried out by conducting distractor analysis on the Jamovi 2.4.11 program to assess the question items and the performance of wrong and correct answers in multiple-choice questions. The reliability test was carried out by reliability analysis with Cronbach's ???? scale in the Jamovi 2.4.11 program. The validity evidence through expert judgment by 3 grade 5 elementary school teachers in Malang City. The results of this study indicate that the characteristics of the mathematics test in the category of item difficulty levels in percentage terms are dominant, and the items of the triggers are quite effective. The reliability of the instrument developed has a high level based on Cronbach's analysis of 0.74 and McDonalds analysis of 0.75. AbstrakTes prestasi akademik menjadi instrumen penting untuk mengukur keberhasilan akademik seseorang. Tujuan penelitian ini adalah untuk pengembangan tes prestasi matematika kelas V SD. Responden dari penelitian ini adalah 92 siswa kelas lima sekolah dasar (SD) negeri di Kota Malang. Metode analisis data dilakukan dengan melakukan distractor analysis pada program Jamovi 2.4.11 untuk menilai aitem soal dan kinerja jawaban yang salah dan benar dalam soal pilihan ganda. Uji reliabilitas dilakukan dengan analisis reliabilitas dengan skala Cronbach’s ???? pada program Jamovi 2.4.11. Bukti validitas melalui expert judgement oleh 3 orang guru SD kelas 5 di Kota Malang. Hasil dari penelitian ini menunjukkan bahwa karakteristik tes Matematika pada kategori tingkat kesulitan butir dalam persentase adalah dominan butir pengecoh cukup efektif. Reliabilitas instrumen yang dikembangkan memiliki tingkat yang tinggi berdasarkan pada analisis Cronbach sebesar 0,74 dan analisis McDonalds sebesar 0,75.